Technology Integration in Christian Religious Education Teacher Professional Development to Produce Scientific Writing - Simanjuntak, Junihot M. (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2023)
Scientific writing is one of the tasks in the professional development of teachers and the requirements for promotion outlined by the Ministry of Education in Indonesia. Producing scientific writing requires skills, and this is a trending issue among Christian religious education subject teachers in Indonesia today, how they struggle to develop effective scientific writing. At present, in private and other public schools, it is common for teachers to produce writing using digital technology. However, this has not happened for teachers of Christian religious education subjects. Integrating technology in schools by Christian religious education subject teachers can help improve writing initiatives and skills that focus on writing pedagogy. This initiative will provide technical support to teachers of Christian religious education so they can focus on writing scientific papers. Professional development of teachers in the subject of continuing Christian religious education based on scholarly writing will emphasize how to utilize digital tools to deliver evidence-based writing instructions. Christian Religious Education subject teachers gain the most when given systematic and explicit instruction in science-based strategies for writing and the writing process, and how to make effective use of digital tools as part of the scientific paper writing process.